1993
DOI: 10.1002/j.1537-2197.1993.tb13837.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Spatial Features of Clones in a Population of Bracken Fern, Pteridium Aquilinum (Dennstaedtiaceae)

Abstract: Allozymes were used to study the spatial attributes of clones (genets) comprising a population of Pteridium aquilinum (L.) Kuhn var. latiusculum (Desv.) Underw. ex Heller (bracken fern) in the Appalachian Mountains of Virginia. Ramets (individual leaves) were sampled at intervals of 165 m (or less in some cases) and genotyped for six polymorphic isozyme loci to produce a map depicting the spatial patterning of genets. Forty-five distinct genotypes were detected, 14 of which were sampled more than once, five of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
269
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(274 citation statements)
references
References 28 publications
(29 reference statements)
2
269
0
3
Order By: Relevance
“…Hardy-Weinberg equilibrium was assumed (see Results) in the calculation of ISSR allele frequencies used in estimating H e . The probability of occurrence of a multilocus ISSR genotype (assuming no genetic linkage) was determined following Parks and Werth (1993) and Montalvo et al (1997).…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardy-Weinberg equilibrium was assumed (see Results) in the calculation of ISSR allele frequencies used in estimating H e . The probability of occurrence of a multilocus ISSR genotype (assuming no genetic linkage) was determined following Parks and Werth (1993) and Montalvo et al (1997).…”
Section: Data Analysesmentioning
confidence: 99%
“…Allozymes (reviewed in Ellstrand and Roose 1987; see also Parks and Werth 1993;Montalvo et al 1997;Mayes et al 1998;Pappert et al 2000), anonymous DNA markers (Hsiao and Rieseberg 1994;Stewart and Porter 1995;Stiller and Denton 1995;Steinger et al 1996;Olfelt et al 1998;Suzuki et al 1999;Corradini et al 2002) and a combination of both methods (Waycott 1995;Ayres and Ryan 1997;Esselman et al 1999;Ge and Sun 1999) have been effectively used in studies of clonal plant populations. Molecular methods are also valuable tools for identifying levels of genetic variation within and among plant populations, providing information that can be used to infer their reproductive systems and demographic histories.…”
Section: Introductionmentioning
confidence: 99%
“…They found a mean value of 0.17 for all 21 species. In other studies Pornon et al (2000) found a PD of 0.16 to 0.18 in Rhododendron, while Suyama et al (2000) found 0.43 for dwarf bamboo and Parks and Werth (1993) calculated a value of 0.51 for bracken fern. In this study we calculated a PD value of 0.22.…”
Section: Similarity Thresholdmentioning
confidence: 92%
“…Fig. 6) Trees encounter of a specific genotype by sexual reproduction in a random mating population was calculated as P se = 1-(1 -P gen ) N , where N is the number of distinct genets (Parks and Werth 1993). The area covered by each genet (n C 11) was measured in Adobe Reader version XI based on the plot maps.…”
Section: Clone Identificationmentioning
confidence: 99%
“…In order to assess the accuracy of genetic clonal identification, genotype probability was calculated as P gen = ( Q p i )2 h , where p i is the frequency of each allele in the multi-locus genotype, and h is the number of heterozygous loci, which gives the probability of two ramets that belong to different genets having the same genotype by chance (Parks and Werth 1993;Sydes and Peakall 1998). In addition, the probability of a second Leaf length ratio LR Leaf length from the leaf base to the widest part of the leaf divided by leaf length from the widest part of the leaf to the leaf tip (suppl.…”
Section: Clone Identificationmentioning
confidence: 99%